Consumer adoption of internet banking in the case of Malayan Banking Berhad / Firzera Erkafirnie Yusuf - Yusuf, Firzera Erkafirnie (2018)
This research will study about the consumer adoption of Maybank internet banking that focus on the consumers in Kuching. In this chapter it consists the background of study, scope of study, definitions terms and limitation of study.